Entrepreneurial Skills for Smallholder Livestock Keepers: A Training Manual (Amharic) - Ekule, Muluken; Wamatu, Jane; Cherkos, Fikre; G/wold, Abebi; Belayneh, Tesfa (International Center for Agricultural Research in the Dry Areas, 2022)
A Training Manual (Amharic) on the Development of Entrepreneurial Skills for Smallholder Livestock Keepers.